The Urgency of Wasatiyyah Islamic Da’wah in The Development of Muslim Society - Asren Nasution (Sufiya Journal of Islamic Studies, 2025)
Wasatiyah Islamic preaching represents an approach that emphasizes balance, moderation, and justice in conveying Islamic teachings. In today’s complex and pluralistic societies, this approach is highly relevant for maintaining social harmony, preventing radicalism, and reinforcing humanitarian values. The present study aims to examine the urgency of Wasatiyah Islamic preaching in fostering an inclusive, dynamic, and civilized Muslim community. Wasatiyah preaching is not limited to theological aspects but also extends to the social, cultural, and political dimensions of the ummah. The findings indicate that the strategic implementation of Wasatiyah preaching can provide an alternative solution to the challenges posed by globalization and the crisis of religious identity among Muslims.